2019
DOI: 10.1177/1078390319877953
|View full text |Cite
|
Sign up to set email alerts
|

Self-Management Support Needs From the Perspectives of Persons With Severe Mental Illness: A Systematic Review and Thematic Synthesis of Qualitative Research

Abstract: BACKGROUND: The development of de-hospitalization policies in mental health has resulted in a growing emphasis on self-management. In the chronic care model, self-management support is an essential element. Because of the episodic nature of severe mental illness (SMI) and its high relapse rates, we assume that the extent of self-management support needs of individuals with an SMI is considerable. However, a clear overview of the nature of the self-management support needs of persons with SMI is missing. OBJECT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
(212 reference statements)
0
5
0
Order By: Relevance
“…Previous research reported similar results. Information and communication about pharmacological therapy are important points of attention during the treatment process of patients [31][32][33].…”
Section: Main Findingsmentioning
confidence: 99%
“…Previous research reported similar results. Information and communication about pharmacological therapy are important points of attention during the treatment process of patients [31][32][33].…”
Section: Main Findingsmentioning
confidence: 99%
“…However, they rarely talked to other people about their diabetes‐related worries and challenges. Effects of social support and peer‐support have been studied widely among people with either diabetes or severe mental illness and studies have shown that support from social networks and peers can improve self‐management of the illnesses respectively (Beentjes et al, 2020; Carpenter et al, 2019; Degnan et al, 2018; Lloyd‐Evans et al, 2014; Schram et al, 2021). However, literature on social support and peer‐support among people with severe mental illness and type 2 diabetes is sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Although communicative and critical health literacy was reported to be the most crucial factor in facilitating self‐care behaviours in people diagnosed with T2DM (Wang et al., 2016), the effect of health literacy on self‐care behaviours was weaker, possibly because of diabetes distress or depression (Schinckus et al., 2018). Because negative emotional reactions or poor cognitive function may weaken the association between health literacy and self‐care behaviours in people diagnosed with SMI, they require informational and emotional support to reduce the emotional burden of their illness and acknowledge their illness‐related experiences to enable them to perform effective self‐care behaviours (Beentjes et al., 2020).…”
Section: Discussionmentioning
confidence: 99%